Gene migration of giardiasis in Iran; a microevolutionary scale for reflecting transmission patterns of Giardia lamblia assemblages in symptomatic patients. (January 2022) - Spotin, Adel; Mohammadi-ghalehbin, Behnam; Mahami-Oskouei, Mahmoud; Karamat, Majid
Abstract: In the microevolutionary scale of Giardia lamblia, the gene migration indicates how G. lamblia assemblages have transmitted between adjacent counties. 33 positive fecal samples were taken from patients suffering gastrointestinal disorders (nausea, bloating, burping constipation and fatty diarrhea) at Tabriz and Ardabil cities, where located in the cold regions of northwest Iran. Following parasitological examinations, DNA samples were extracted, amplified and digested by single-step PCR-RFLP assay, targeting the glutamate dehydrogenase ( gdh ) locus to distinguish within and between assemblages A and B. PCR products were directly sequenced to reconfirm their heterogeneity traits and phylogenetic analysis. Of the 33 isolates, 81.9% (n: 27), 9% (n: 3) and 9% (n: 3) were successfully identified as assemblages A (genotype AII), B (genotype BIII) and the mixed of genotypes AII and B, respectively. Despite the presence of heterogeneous clinical backgrounds, a low genetic diversity of sub-assemblage AII was identified among symptomatic cases. A low value of pairwise fixation index showed that G. lamblia sub-assemblage AII is not genetically differentiated among northwest regions of Iran. The occurrence of haplotypes TAB-1/ARD-1 between two regional populations indicates that there is a dawn of G. lamblia gene flow due to transfer of alleles through host mobility and/or ecological alterations. To assess the hypothetical evolutionary scenario, further studies are essential for multilocus genotyping of G. lamblia in tropical regions of Iran and neighboring countries. Graphical abstract: Image 1 Highlights: Despite the presence of heterogeneous clinical backgrounds, a low genetic diversity of sub-assemblage AII was identified among symptomatic cases of giardiasis. A low value of F st index indicated that G. lamblia assemblage A is not genetically differentiated among northwest regions of Iran. Findings indicate that there is a dawn of G. lamblia flow due to host mobility or ecological alterations between two regional populations.